Urgensi Pemberatan Hukuman Bagi Residivis Kekerasan Terhadap Anak Sebagai Upaya Perlindungan Hukum Anak Di Indonesia - Azrieliani Vira Annisa; Maroni; Dewi, Erna (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Violence against children is a form of human rights violation that requires serious handling, especially when committed by perpetrators who are recidivists. In the context of criminal law in Indonesia, the aggravation of punishment against perpetrators of child abuse who repeat their actions is still not explicitly regulated in the applicable regulations. In fact, the aggravation of punishment against recidivists is an important step to strengthen the legal protection of children. This research aims to examine the urgency and contribution of aggravated punishment in order to provide more effective legal protection for children as a vulnerable group. Through a normative juridical approach, it is found that the aggravation of punishment for recidivists does not only create a deterrent effect, but also serves as a preventive effort, the formation of a legal culture, and the enforcement of substantive justice. The state has a moral and legal responsibility to tackle violence against children through legal instruments that are clear, firm, and oriented towards victim protection. Therefore, it is necessary to reformulate criminal law policies that explicitly regulate the aggravation of sanctions for recidivists of violence against children so that the criminal justice system can work more effectively, fairly, and humanistically.